Development of Self-Nano Emulsifying Drug Delivery System (SNEEDS) Containing Hibiscus sabdariffa L. Extract, an Anticancer against T47D Cells, as a Co-Chemotherapy of Cisplatin - Nurani, Laela Hayu; Efiana, Nuri Ari; Wahyuningtyas, Nurma; Edityaningrum, Citra Ariani; Indratmoko, Septiana; Guntarti, Any; Ma’ruf, Muhammad (Journal of Food and Pharmaceutical Sciences, 2026)
The first-line chemotherapy drug for breast cancer is cisplatin. However, it shows a high incidence of resistance. Therefore, Hibiscus Sabdariffa L (HS), containing strong anticancer compounds, was developed using a self-nano-emulsifying drug delivery system (SNEDDS), potentially as cisplatin co-chemotherapy. This study aimed to develop the HS SNEDDS providing anticancer activity against T47D breast cancer cells. The methods consist of the development of HS SNEDDS (F1-F7) with various surfactant and co-surfactant concentrations, followed by characterization of HS SNEDDS. The selected formulation was evaluated regarding the cytotoxicity on T47D cells and selectivity on Vero cells. The results showed that F7, as a selected formulation, indicated a transmittance, globule size, PI, zeta potential, and emulsification time of 97.80%, 15.68 ± 0.19 nm, 0.12 ± 0.01, -8.05 ± 1.88 mV, and 24.76 ± 0.29 seconds, respectively. Furthermore, according to the data of toxicity and selectivity studies, HS SNEDDS was proven to enhance the toxic properties of HS extract on T47D cells and be safe on normal cells. In conclusion, HS SNEDDS providing the required characteristics could be obtained, and potentially be used as a co-chemotherapy of cisplatin, showing the cytotoxic effect on T47D breast cancer cells.